Scandinavians on the banks of the Parsęta river: Viking graves in the cemetery at Świelubie in Western Pomerania - Duczko, Władysław (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2020)
A cemetery of more than 100 barrows is located at Świelubie, near the 9th c. stronghold of Bardy lying south of Kołobrzeg in Western Pomerania. In six of the 36 graves that were explored, containing both male and female burials, the grave goods consisted of typically Scandinavian objects. For a long time the discovery posed a problem that was also political in its nature. Author revisits the Scandinavian finds from Świelubie and discusses their cultural attribution and chronology. A close study of the artifacts identified the burials as of Swedes with ties to the trade emporium of Birka on Mälaren lake in central Sweden; the dating of the finds points to the 2nd half of the 9th c.
ill., 24 cm
Keywords: settlements; cemeteries; Scandinavian material culture; weaponry; ornaments; Poland; Pomerania; Świelubie; Birka